Cyclodextrin Curcumin Formulation Improves Outcome in a Preclinical Pig Model of Marginal Kidney Transplantation. Issue 5 (11th March 2014) - Thuillier, R.; Allain, G.; Giraud, S.; SaintYves, T.; Delpech, P. O.; Couturier, P.; Billault, C.; Marchand, E.; Vaahtera, L.; Parkkinen, J.; Hauet, T.
Abstract : Decreasing organ quality is prompting research toward new methods to alleviate ischemia reperfusion injury (IRI). Oxidative stress and nuclear factor kappa beta (NF‐κB) activation are well‐described elements of IRI. We added cyclodextrin‐complexed curcumin (CDC), a potent antioxidant and NF‐κB inhibitor, to University of Wisconsin (UW) solution (Belzer's Solution, Viaspan), one of the most effective clinically approved preservative solutions. The effects of CDC were evaluated on pig endothelial cells and in an autologous donation after circulatory death (DCD) kidney transplantation model in large white pigs. CDC allowed rapid and lasting uptake of curcumin into cells. In vitro, CDC decreased mitochondrial loss of function, improved viability and lowered endothelial activation. In vivo, CDC improved function recovery, lowered histological injury and doubled animal survival (83.3% vs. 41.7%). At 3 months, immunohistochemical staining for epithelial‐to‐mesenchymal transition (EMT) and fibrosis markers was intense in UW grafts while it remained limited in the UW + CDC group. Transcriptional analysis showed that CDC treatment protected against up‐regulation of several pathophysiological pathways leading to inflammation, EMT and fibrosis. Thus, use of CDC in a preclinical transplantation model with stringent IRI rescued kidney grafts from an unfavorable prognosis. As curcumin has proved well tolerated and nontoxic, this strategy shows promise for translation to the clinic. Abstract : In a preclinical pig model of marginal kidney transplantation, graft quality and outcome are improved by supplementing University of Wisconsin solution with a cyclodextrin curcumin formulation.